İz bölgesi - İlday, Özlem (Fen Bilimleri Enstitüsü, 1991)
Havacılıkta bir çok şekilde kullanılan eksene! simetrik cisimlerin uçuş perfor manslarını ve manevra kabiliyetlerini arttırmak ve bazı aerodinamik temel problem lere açıklık kazandırmak için farklı geometrik şekilleri olan cisimlere ait akım alanı ve aerodinamik kuvvet sistemi farklı şartlarda incelenmelidir. Bu tezde, geometrik şekilleri farklı ve eksenel simetrik olan roket tipi bazı cisim lere ait iz bölgesi deneysel olarak incelenmiştir. Elde edilen sonuçlar yardımıyla da cisimlere ait sürükleme hesaplanmıştır. 8u tez beş ana bölümden meydana gelmiştir. Bölüm l'de konunun önemi izah edilmiş ve tezin amacı, kapsamı verilmiştir. Bölüm 2, genel bilgilere ve konuyla ilgili ulaşılabılınen literatüre ayrılmıştır. Bölüm 3, deneysel incelemenin anlatıldığı bölümdür. Deney tekniği ve sonuçların irdelenmesi bu bölümde anlatılmıştır. Bölüm 4, deneysel sonuçlara dayanılarak cisimlere ait sürükleme katsayılarının tayinine bu bölümde yer verilmiştir. Momentum teoremi ve yöntemi anlatılarak uygu laması gösterilmiştir. Çalışmanın özünü, cisimlerin iz bölgesinin kantitatif olarak incelenmesi mak sadıyla yapılan sıcak tel deneyleri oluşturmaktadır. Sıfır hücum açısı halinde yapılan bu deneyler vasıtıyla cismin taban geometrısındekı bazı değişikliklerin akım alanına etkisi ortaya konmuştur. Ayrıca, eksenel simetrik iz bölgesinin fiziksel yapısıyla ilgili olarak aydınlatıcı bilgiler elde edilmiştir. Sonuç bölümünü oluşturan Bölüm 5'te, bu tezde elde edilen sonuçlar bir bütün olarak gözden geçirilmiş ve maddeler halinde sunulmuştur.

It is necessary to investigate the flow field and aerodynamic force system of bodies with different shapes in different conditions in order to improve flight performances and maneuvering capabilities of axisymmetrical bodies, which are used in many ways such as missiles, rockets, fuselage of aircraft and airships. Requirements in the aerospace technology for increasing the reliability and performance, and the new developments in research opportunities cause a intensely need of new studies. Due to this need various investigations are going on out throughout the world. This work is one of these investigations. In the direction of the need mentioned above, it was intended to obtain experi mental data. Similar studies can be seen in the literature, but for the geometries used in this study and at low subsonic speeds, experimental data are not present. Again, si milar studies in I.T.U. Laboratories were carried out, but until present study computer was not used for collecting hot wire data directly. It was aimed to do the experiments by using such a system in I.T.U. Aerodynamics Laboratory. The present study consists of five main sections. In Chapter 1, the importance of the subject was explained. The purpose and the contents of this thesis were also given. In the present study, the wake region of some rocket-type bodies, which are axisymmetric different geometrical shapes, were investigated experimentally. Experi- XImerits were conducted in I.T.U. 50x50 subsonic open circuit wind tunnel with a test section of 50x50x200 cm. All the tests were carried out of a freestream velocity of K» =10 m/s. Freestream turbulence level was 0.3%. A CTA hot wire system of DISA 55M10 (55M01 Main Unit, 55M05 Power Pack, 55D25 Auxiliary Unit, 55D35 RMS Unit, 55D15 Linearizer ve 52A40 Power Supply) was employed with an automatic traversing mechanism. The analog output of this system wasdigitized by a data acqui sition unit (Validyne DAS 380 analog/digital converter) and transferred to a personal computer with a 80386 microprocessor for evaluating the data. The mean velocity and turbulence measurements were done along the symmetry axis of the models at zero angle of attack. The same quantities were also measured along the cross lines of the wakes of the models at several stations from the base. Chapter 2 is devoted to the general informations and the available studies. Flow separation causes a wake behind the body. The wake of a axisymmetric body with an angle of attack is three dimensional and has very complex structure. In spite of this, a body of the same type with zero angle of attack has a wake of an axisymmetric and relatively simple structure. Indeed, to study axisymmetric wake is more difficult than two dimensional wake. To investigate the wake behind a slender axisymmetric body whit a blunt base, at zero angle of attack is very important, because the aerodynamic characteristics of such a body depends on the structure of the wake. The structure of the wake highly depends upon many parameters such as Mach number, Reynolds number, the geometric shape of body and the structure of the boundary layer which approaches to the wake. The wake is related with drag of the body, because the same factors also affect the drag. Indeed, the drag of a body which has a wider wake is greater than that with smaller wake. The structure of the wake for an axisymmetric body with blunt base has a near- wake region and a far-wake region. The region, covered with the surface of the base and the free shear layer is called as "recirculation region*. The near-wake region consists of the recirculation region and the rear-stagnation point which is sometimes called as Xll"reattachment point*. In Chapter 3 the experimental investigations in this work were explained. First, the experimental technique is outlined and then the experimental results were presented with the discussions. The results may be outlined as follows: 1- The geometrical modifications at the base of a body have no significant effect in the far-wake region, although they highly affects the near-wake region. 2- It was also observed that the distance between the base and the rear stagnation point for bodies with blunt base (Model 1) and nozzle-type base (Model 4) is approx imately 1.1 times of the maximum diameter of the body. For the other models with truncated conical base (Model 2) and boat-tailed base (Model 3) this value is smaller due to the length of the recirculation region behind the base. 3- Another interesting point is that the maximum centeriine velocity of the re versed flow in the near-wake region takes place at about 60% of the distance between the base and the rear stagnation point, from the base. 4- The cross mean velocity and turbulence profiles at any station of the wake indicates that the point where the turbulence has a maximum value corresponds to the point where the mean velocity profile has an inflation point. 5- The far-wake region diverges in the main flow direction. 6- Near the rear-stagnation point, the maximum value of the turbulence is ap proximately 15%. This value is also the maximum value in the whole wake region. However, this value is greater for Model 4 with nozzle-type base geometry, as 22%. The turbulence in the wake reaches a maximum value on a circle around the rear xmstagnation point. Tike radius of this circle is about 90% for Model 4 and 65-75% for other models. In Chapter 4 the drag coefficients «ere calculated from the cross mean velocity and turbulence profiles employing the Momentum Method. These calculations indi cated that drag coefficients of models with conical base (Model 2) and boat-tail type base (Model 3) are smaller than those of the models, which have blunt base (Model 1) and nozzle-type base (Model 4). Of the forces and moments acting on a body, the drag force is most influenced by the viscosity of the medium in which the body is traveling. Therefore, the drag force is the most difficult one to predict or to measure accurately. The theoretical tools used to predict drag must take the viscosity into account. There are1 many components of drag depending on many factors constituting the total drag. The pressure drag caused by the static pressure acting on the body, the skin friction drag caused by the viscous shear stresses on the surface of the body and the base drag which depends on the base geometry of the body are some of them. For the calculation of the total drag of a body all the drag components must be predicted and added together. Generally, it is used different methods theoretically and experimentally for the prediction of each drag component, because the reasons forming the drag components, the validity of the methods in the theory and the measurement techniques in the experiments are different. As it can be seen it is very troublesome to predict the total drag. In this work, it was used a method which is easy to apply and give significant results, for the drag prediction, the Momentum Method. It is possible to calculate the drag of a body by choosing a proper control volume around the body and by applying the momentum theorem using the mean velocity and turbulence profiles obtained ex perimentally in the wake of the body. This method is used often for 2D or axisymmetric wakes to predict the drag, because the drag obtained via this method is the total drag acting on the body. " In the present study, a control volume which has parallel surfaces, was choosen xiv\ and for the drag coefficient -//^<)-//?-1'4'+2//S4) was obtained. And for the axisymmetrical bodies this definition becomes -CD = ~P-PS.. t W,TJ.xr"r..,fvF Çoo 5İ '^Jh^-^i^Jki"^ By applying the measured values in specified conditions to this equation the drag coefficients of four models were calculated. In Chapter 5, which is the last one, the results obtained in this thesis were rewiewed and discussed.
Wake flow
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: eksenel simetrik cisimler; sürükleme katsayısı; iz akışı; Axial symmetric bodies; Drag coefficient; Wake flow